Improving Web Color using Color Scheme Assessment Tool (COSAT) - Nurul Wahidah, Mohd Zin; Mazlina, Abdul Majid; Fakhreldin, Mohammed Adam Ibrahim (2015)
Nowadays, usability of a user interface becomes extraordinary important. We cannot underestimate the measuring of usability because it can reveal the qualities of the product in term of its functionality, which usually arises during the design phase. Therefore, usability is crucial to be considered when developing a system. Color has an important role to increase the usability of a web page. The use of proper color on interface design can greatly enhance the user attention which will help to enhance the usability of software. According to the existing web design guidelines, color combination, color contrast and color position are the three main features to be considered in web color design. From the existing usability tools on web color checking, we found a research gap on the usability tools which reflect to the three main features of color consideration in web page. Until now, there is no tool exists that combined these main features. Thus, this paper is aimed to develop a usability tool namely Color Scheme Assessment Tool (COSAT) that follows the guidelines of color combination, color contrast and color position.